Group Guidance with Cooperative Games to Improve Social Skills in Junior High School Students - Yola Noperiyanti; Ali Daud Hasibuan (MASI Mandiri Edukasi, 2025)
The issue of low social skills among junior high school students can hinder interpersonal relationships and collaboration during the learning process. This study examines the effectiveness of group guidance services that integrate cooperative game techniques in improving the social skills of seventh-grade students at SMP Negeri 3 Galang. A quantitative approach was employed using a quasi-experimental design of the Pretest-Posttest Control Group type. The study population consisted of 101 students, with 16 students identified as having low social skills. The sample was divided into experimental and control groups, each comprising eight students selected through purposive sampling. The intervention was conducted over six sessions. The research instrument used was a social skills scale, and the data were analysed using the t-test with the assistance of SPSS version 27. The analysis results showed a significance value (2-tailed) of 0.000 (< 0.05), indicating a significant difference between the experimental and control groups. The t-values were 17.616 and 8.981, with a significance level of 0.000. These findings demonstrate that group guidance services based on cooperative games effectively enhance students' social skills. This result implies that such an approach can serve as an alternative strategy for school counselling services.